Young Investor Dominance, Overconfidence, Risk Tolerance, And Stock Investment Decisions - Alfianti Arung Badeng; Maiercherinra Daud (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the influence of young investor dominance and overconfidence on stock investment decisions, with risk tolerance positioned as a mediating variable. The study applies a quantitative survey design using structured questionnaires distributed to individual stock investors in Indonesia. The empirical data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that young investor dominance has no significant effect on either risk tolerance or stock investment decisions. Risk tolerance also fails to mediate the relationship between young investor dominance and stock investment decisions. In contrast, overconfidence has a positive and significant effect on risk tolerance and stock investment decisions. Risk tolerance also has a positive and significant effect on stock investment decisions and mediates the effect of overconfidence on stock investment decisions. These findings suggest that psychological factors, particularly overconfidence and risk tolerance, are more decisive than demographic dominance in shaping investment behaviour. Theoretically, this study strengthens the behavioral finance perspective by showing how cognitive bias and risk preference jointly influence stock investment decisions. Practically, the results imply that regulators and market stakeholders should strengthen investor education by integrating financial literacy, psychological bias management, and risk-profile awareness.